Um plano de métricas para monitoramento de projetos scrum - Spies, Eduardo Henrique (2013)
Agile methods have earned their space both in industry and in academia, being increasingly used. With the focus on frequent returns to customers, these methods have difficulties to gain control and maintain efficient communication, especially in larger projects with several collaborators. Software engineering techniques have proved of great value to increase predictability and provide more discipline to this kind of projects. In this paper we present a metrics program for SCRUM and an extension of a Data Warehousing environment for monitoring projects. Thus, we provide a consistent repository that can be used as a historical reference of projects and for exploring metrics in different dimensions, easing control over all aspects of the progress of a project.